2015
DOI: 10.4274/tod.93064
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Physical Therapy Accompanying Exercise with Only Exercise Treatments in Patients with Chronic Mechanical Low Back Pain

Abstract: Objective: Investigating and comparing the effects of exercise and physical therapy accompanying exercise treatments in patients with chronic low back pain. Materials and Methods: Twenty three patients with mechanical type low back existing more than 3 months were included one of the exercise or the physical therapy+exercise groups according to their application sequence. Both of the groups performed lumbar flexion and extension exercises, strengthening of the lumbar and abdominal muscle exercises and iliopsoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Of these, 475 were excluded, and 55 were exposed to a thorough review of the full article. Twenty-two studies were excluded after the review of the full article because of a lack of randomization, [26][27][28][29][30][31][32][33][34] using different study designs, 35,36 the lack of a control group, 37,38 different study populations (comparing two different treatments with one including ICF), 39,40 lack of the required outcome measures, [41][42][43] different languages, 44,45 inaccessibility of the full article, 46 and a lack of the desired intervention. 47 The final results included 33 trials in addition to two other trials 12,48 that were added after the manual search of the reference list (see Supplemental Digital Content 3, http://links.lww.com/ PHM/B380).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 475 were excluded, and 55 were exposed to a thorough review of the full article. Twenty-two studies were excluded after the review of the full article because of a lack of randomization, [26][27][28][29][30][31][32][33][34] using different study designs, 35,36 the lack of a control group, 37,38 different study populations (comparing two different treatments with one including ICF), 39,40 lack of the required outcome measures, [41][42][43] different languages, 44,45 inaccessibility of the full article, 46 and a lack of the desired intervention. 47 The final results included 33 trials in addition to two other trials 12,48 that were added after the manual search of the reference list (see Supplemental Digital Content 3, http://links.lww.com/ PHM/B380).…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies applying combined physiotherapy programmes in the literature. Yılmaz et al 22 applied combined physiotherapy (10 sessions of HP + US + interferential current + exercise) to patients with mechanical low back pain for >3 months, and reported that the increase in the joint range of motion as well as the decrease in pain and disability were significantly higher. Koldaş Doğan et al 23 reported that exercise training applied in addition to a combined physiotherapy program (HP + US + TENS) was more effective in reducing pain and improving disability and psychological disorders than exercise training alone.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise programs strengthen the treatment, even more, when applied with other physical therapy modalities. It is especially emphasized that the exercise program has a very important place in the chronic low back pain treatment protocol 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%